Wujud Aspek Psikologis dalam Sajak Penyair Jambi Ari Setya Ardhi - Sainil Amral; Sumiharti Sumiharti (Universitas Batanghari Jambi, 2023)
The purpose of this study is to describe the form of conveying the psychological aspects of the psychiatric form contained in the poems of the Jambi poet Ari Setya Ardhi. Jambi poet means a poet who lives in the Jambi area, actively works, and always documents his rhymes in individual anthologies and joint anthologies. This research includes descriptive research with a content analysis approach to documents in the form of literary works. The data in this study are rhyme texts that refer to the psychological aspects of the psychiatric form of depression and the psychiatric form of anxiety. The results showed that in the poems of the Jambi poet Ari Setya Ardhi depression was identified through the use of sounds, word choices, complete text, typography, and the use of imagery